Reflective Thinking for Quality Mathematics Instruction: A Study on Fiji Primary School Teachers’ Knowledge of Reflective Teaching - Raiula, Taraivini Raramasi; S.N, Vijayakumari.; Alasa, Victor M.; Takiveikata, Sereima; Shirotriya, Awadhesh K. (International Journal of STEM Education for Sustainability, 2022)
This study was aim at analyzing the notion of quality teaching expected of teachers as reflective practitioners, which are continuously articulated during workshops, conferences, however, its practicality seems vaguely defined and at times, reflection seems to lose its purpose and value. The study engaged a descriptive survey which used stratified sampling technique which understudies 363 Primary School Teachers in Fiji from the four major Education Divisions, in which each stratum was selected. A ‘Test on Knowledge of Reflective Teaching,’ and a ‘Rating Scale on Practice of Reflective Teaching’ were conducted and analysed to compare the components of Knowledge and Practice of Reflective Teaching, with respect to teaching experience, and the data was analysed quantitatively using Analysis of Variance (ANOVA). Fndings from the study amongst others is that there is a significant difference in knowledge which focus on practical aspects’ component of knowledge of reflective teaching for primary mathematics teachers in Fiji.